2013
DOI: 10.1099/mic.0.068734-0
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of the tyrothricin production profile of Bacillus aneurinolyticus

Abstract: A group of non-ribosomally produced antimicrobial peptides, the tyrocidines from the tyrothricin complex, have potential as antimicrobial agents in both medicine and industry. Previous work by our group illustrated that the more polar tyrocidines rich in Trp residues in their structure were more active toward Gram-positive bacteria, while the more non-polar tyrocidines rich in Phe residues had greater activity toward Plasmodium falciparum, one of the major causative pathogens of malaria in humans. Our group al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 62 publications
0
28
0
Order By: Relevance
“…The tyrocidines were purified and analyzed for purity as described previously. De novo sequencing using electrospray mass spectrometry by Vosloo et al (34) and Spathelf (35) confirmed the identities of the tyrocidines and analogues. All the tyrocidines (TrcA, TrcB, TrcC, TpcC, and PhcA) used in this study had purities of Ͼ90% according to ultraperformance liquid chromatography linked to high-resolution electrospray mass spectrometry (see Table S1 in the supplemental material).…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…The tyrocidines were purified and analyzed for purity as described previously. De novo sequencing using electrospray mass spectrometry by Vosloo et al (34) and Spathelf (35) confirmed the identities of the tyrocidines and analogues. All the tyrocidines (TrcA, TrcB, TrcC, TpcC, and PhcA) used in this study had purities of Ͼ90% according to ultraperformance liquid chromatography linked to high-resolution electrospray mass spectrometry (see Table S1 in the supplemental material).…”
Section: Methodsmentioning
confidence: 93%
“…The percent leakage [F(%)] after 1 min was calculated by the following formula 100(%) (I Ϫ I 0 )/(I 100% Ϫ I 0 ), where I is the intensity observed in the peptide solution, and I 0 and I 100% are the fluorescence intensities measured in the absence of peptide and in the presence of Triton X-100, respectively (41). (29) and the identities were confirmed by our group (34,35). c Detected monoisotopic M r of peptides determined from purified peptides using highresolution time of flight-electrospray mass spectrometry (TOF-ESMS) (refer to Table S1 in the supplemental material).…”
Section: Methodsmentioning
confidence: 95%
“…The five tyrocidines and analogues, as well as the Trc mixture used in this study were obtained from the same stocks used by Troskie et al [5] and had purities >90% according to ultraperformance liquid chromatography linked to high resolution electrospray mass spectrometry (UPLC-MS), as described previously [24]. Gramicidin S (97.5% purity according to manufacturers, 94% purity according to our UPLC-MS studies) was supplied by Sigma (St Louis, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Vosloo et al () established that the natural production of different tyrocidine analogues could be manipulated through supplementation of the growth medium of Br. parabrevis with the two aromatic amino acids (Aaa) Phe and Trp, while supplementation with Tyr, Cys, Lys and Arg had no noteworthy influence on the production or peptide profile.…”
Section: Introductionmentioning
confidence: 99%